THE EFFECTIVENESS OF VIDEO PROJECT TO IMPROVE STUDENTS’ SPEAKING SKILL AT ELEVENTH GRADE STUDENTS OF SMA MUHAMMADIYAH 9 MAKASSAR - Agri Busman, Dian; Nurdevi Bte Abdul; Saiful (Jurnal Keguruan dan Ilmu Pendidikan (JKIP), 2019)
This research aimed at finding out the effectiveness of the students’ speaking skill by using Video Project as media in teaching at Eleventh Grade Students of SMA Muhammadiyah 9 Makassar.This research used Pre-experimental Design with one group pre-test and post-test design. The sample of the research was class XI MIA of SMA Muhammadiyah 9 Makassar taken by purposive sampling technique which consisted of 15 students.The research findings indicated that using Video Project was effective in improving the students’ speaking skill in term of fluency. It was proved by the means score in terms of fluency of pre-test was 72. 2 and means score of post-test 82. 26. It means that, the means score of post-test was greater than the means score of pre-test. Then the improvement of the students’ speaking skill in terms of fluency was 13. 57 %.Then the calculating the value of t-test in fluency was greater than t-table value (14. 7 > 1.761). (H1) is accepted and null hypothesis (H0) is rejected. Thus, the researcher concluded that there was significant difference between pre-test and post-test by teaching students using video project in speaking skill of SMA Muhammadiyah 9 Makassar.